The influence of host ecology and land cover change on rabies virus epidemiology in the Flint Hills - Bowe, Sarah Elizabeth (Kansas State University, 2009)
As human populations increase world-wide, land use and land cover are altered to support the rapid anthropogenic expansion. These landscape alterations influence patterns of zoonotic infectious disease emergence and propagation. It is therefore becoming increasingly important to study emerging and re-emerging diseases to predict and manage for future epidemics. Studies of directly-transmitted infectious diseases should consider three components of disease epidemiology: characteristics of the pathogen, ecology of the host, and habitat configuration of the underlying landscape. I studied the influence of both the host ecology of the striped skunk (Mephitis mephitis) and the alteration of the underlying landscape on the epidemiology of rabies virus in the Flint Hills of Kansas. This tall-grass prairie is experiencing woody expansion due to anthropogenic disturbance, altering the landscape on which the rabies virus emerges and spreads. We first studied the behavioral and social ecology of the striped skunk using field and genetic methods. We concluded that 1) striped skunks reached high population densities in anthropogenically disturbed habitats, 2) these individuals were not closely related, and 3) contact rates could be influenced by temperature. Using habitat-specific skunk densities from this initial study, we created spatially-explicit contact networks of skunk populations across the Upper Kansas River Watershed and simulated the emergence and spread of rabies through the system. This modeling approach revealed a threshold of forest habitat beyond which striped skunks became increasingly connected and the rabies virus reached greater extents across the landscape. Based on these findings we recommend fire regimes and land cover alterations to reduce woody encroachment across the Flint Hills and to avoid future disease epidemics in the region.
Keywords: Mephitis mephitis; Rabies virus; Epidemiological network modeling; Woody encroachment; Flint Hills; Biology, Ecology (0329)